Production And Extraction Of Astaxanthin From Microalgae Haematococcus Pluvialis Under Different Stress Conditions In Bbm And Rm Culture Media. (@limentech, Ciencia y Tecnología Alimentaria, 2024)
Microalgae are an important source of bioactive compounds useful at an industrial level, an example of this is astaxanthin, a natural carotenoid pigment known for its beneficial properties and its potential synthesis in the microalga Haematococcus pluvialis. The main objective of this research work was to evaluate the production and extraction of astaxanthin through two tests using different culture media which were the modified BBM medium and RM medium inoculated with the reference strain UA of H. pluvialis underspecific stress conditions that were key for the production of the carotenoid, which includes the addition of sodium acetate at a concentration of 1,6 g / L after 22 days of culture, the extraction of astaxanthin using soybean oil / ethanol, the quantification of astaxanthin and chlorophyll by spectrophotometry and finally the ANOVA statistical analysis was carried out. At the end of both tests, it was concluded that the production of astaxanthin in the microalgae was higher in the BBM medium supplemented with sodium acetate compared to the production in the non-supplemented RM medium, with production of 34,01 ug/ml and 25,74 ug/ml respectively. Likewise, it was determined that the extraction of astaxanthin using the soybean oil/ethanol dissolution method is a viable, sustainable, and economical technique, and could be of great interest for future research and for its application in industrial processes related to the production of astaxanthin.
Keywords: Astaxanthin; Haematococcus pluvialis; sodium acetate; soybean oil; stress factors